Disfunção temporomandibular e fatores associados em idosos institucionalizados - Pauletti, Roberta Neuwald (2017)
Temporomandibular disorders are among the diseases most frequently observed with the elderly. It is a set of clinical problems involving the masticatory muscles, the temporomandibular joint and associated structures. It is a disorder, which may be accompanied by pain in the muscles, and in the temporomandibular joints. The associated hard and soft tissues also may include limitations or deviations in amplitude and opening mandibular movements, facial pain or headache. Due to the rapidly, increasing number of elderly in Brazil, demand for long-term care facilities is growing. Along with this growth, the oral health of the residents is very poor and in need of vast improvement. Because of this deficit and a scarcity in studies related to this topic, more investigative work, aimed at evaluating the conditions facing the institutionalized elderly, is required. This requirement is important considering the presence of temporomandibular dysfunction and related variables. This study was carried out with 80 institutionalized elderly, in the municipalities of Passo Fundo and Bento Gonçalves - RS. In order to classify the presence and severity of temporomandibular dysfunction, the Anamnestic Index of Fonseca was used, and a physical examination was performed. It was considered, at the outcome, that there was the presence of temporomandibular dysfunction and independent variables, and thus was of sociodemographic and clinical importance. For analysis, absolute and percentage frequency measures were used. To evaluate the association between TMD and other variables, chi-square and Fisher's Exact Test were used, with a 95% confidence interval and a significance level of 5%. These results led to a scientific study entitled "Prevalence and factors associated with temporomandibular disorder in institutionalized elderly" and is a cross-sectional study showing the prevalence of 56.4% TMD, and association with pain when chewing, bad dentures, headaches, muscle fatigue, neck pain, ear pain, noises and pain in the temporomandibular joints, ringing in the ears and dizziness (p≤0,05). It was found in the search results that more than half of the evaluated subjects had some degree of TMD, and some signs and symptoms associated with the disease such as pain and joint noises, dizziness, tinnitus, facial myalgia, headache, among others. It concluded also that there is a need for further research to address the lack of studies in this area with an aim to improving the quality of life for the elderly.